Optimization of protein extraction from the yeast Saccharomyces cerevisiae - Oliveira, Antonio Martins; Gómez, Raul Jorge Hernan C. (Semina: Ciências Agrárias, 2005)
This work aimed to determine the optimum temperature, pH and sodium chloride sodium concentration for protein extraction of yeast cells during autolysis process. The cellular extract was obtained using commercial compressed baker's yeast Saccharomyces cerevisiae and for statistical analysis and definition of the variation levels of temperature (32,0 to 52,0Â°C), pH (1,32 to 7,00) and NaCl (2,0 to 75%) the Response Surface Analysis Methodology was used. The result obtained showed that the best extraction conditions were: temperature between 49,0 and 51,0Â°C combined with pH values between 3,8 and 5,0 and sodium chloride concentration between 10,0 and 12,0% (w/v), however, sodium chloride concentration higher than 12% was not recommended.